2015
DOI: 10.1007/s40489-014-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Single-Case Research on Teaching Functional Living Skills to Individuals with ASD

Abstract: A meta-analysis of 52 studies teaching functional living skills to individuals with autism spectrum disorder was conducted. Using the Tau effect size with the Dunn and the KruskalWallis post-hoc analyses, the following categories were analyzed: age, diagnosis, intervention type, dependent variable, setting, and implementer. Analyses for age yielded statistically significant findings supporting greatest outcomes for elementaryaged individuals compared to secondary-aged individuals as well as adolescents and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 85 publications
1
14
0
1
Order By: Relevance
“…As discussed above, systematic reviews provide helpful information on the characteristics and overall outcomes of the studies examined in the reviews. However, compared to meta-analytic reviews, the systematic reviews provide limited information on moderating variables that could help school-based teams choose interventions that are feasible and relevant to the needs of the targeted students and reduce the time required by school personnel who are responsible for implementing the interventions (Charlop-Christy et al, 2000;Ninci et al, 2015). Although the current literature on Tier 2 behavior interventions provides limited information concerning moderator effects on outcomes of intervention, several meta-analyses on school-based behavior interventions provide useful information on potential variables that may moderate behavior interventions.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, systematic reviews provide helpful information on the characteristics and overall outcomes of the studies examined in the reviews. However, compared to meta-analytic reviews, the systematic reviews provide limited information on moderating variables that could help school-based teams choose interventions that are feasible and relevant to the needs of the targeted students and reduce the time required by school personnel who are responsible for implementing the interventions (Charlop-Christy et al, 2000;Ninci et al, 2015). Although the current literature on Tier 2 behavior interventions provides limited information concerning moderator effects on outcomes of intervention, several meta-analyses on school-based behavior interventions provide useful information on potential variables that may moderate behavior interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Structured criteria available from the What Works Clearinghouse systematize quality indicators of experimental control and evidence of effectiveness for single-case research designs (Kratochwill et al, 2010(Kratochwill et al, , 2013. These criteria have been adopted in a protocol to structure decision making for which acceptable levels of IRA have been found between two independent raters (Maggin, Briesch, & Chafouleas, 2013;Ninci et al, 2015), supporting the idea that elucidating the specific constructs that raters are evaluating could improve IRA between visual analysts.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the Tau or Tau- U nonoverlap effect size showed general consistency with visual analysis indicators (Ledford, King, Harbin, & Zimmerman, 2018; Ninci et al, 2015). The Tau nonoverlap effect size is a robust measure of nonoverlap of all pairs of data points between two conditions (Parker, Vannest, Davis, & Sauber, 2011b).…”
mentioning
confidence: 76%
“…The Tau nonoverlap effect size is a robust measure of nonoverlap of all pairs of data points between two conditions (Parker, Vannest, Davis, & Sauber, 2011b). A number of meta-analyses have used the nonparametric statistics of Tau or Tau- U (that controls for baseline trend) and nonoverlap of all pairs (NAP, which differs from Tau/Tau- U in scale; Parker, Vannest, & Davis, 2011a) to measure effects (e.g., Ledford et al, 2018; Ninci et al, 2015; Roth, Gillis, & DiGennaro Reed, 2014). These methods fit the assumptions of single-case design and consider all data (Parker et al, 2011a, 2011b).…”
mentioning
confidence: 99%